Control of the electrochemical and photophysical properties of N-substituted benzo[ghi]perylene derivatives. (22nd August 2017) - Tokuo, Kokichi; Sakai, Hayato; Sakanoue, Tomo; Takenobu, Taishi; Araki, Yasuyuki; Wada, Takehiko; Hasobe, Taku
Abstract : Orientation of the lone-pair of electron-dependent electrochemical and photophysical properties were successfully observed by using a series of N -substituted benzo[ ghi ]perylene derivatives. Abstract : In this work, we report the synthesis, and electrochemical and photophysical properties of a series of N -substituted benzo[ ghi ]perylene (BP) derivatives. The orientation of the lone-pair of electrons toward the aromatic core is expected to have a great effect on the electronic structures and energy levels. Namely, the introduction of electron-withdrawing nitrogen atoms and imide groups stabilized the energy levels of the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) in 7, 8-diazabenzo[ ghi ]perylene (DABP) and 7, 8-diazabenzo[ ghi ]peryleneimide (DABPIm) because of the parallel orientation to the aromatic ring plane. This is in sharp contrast with the decreased trend of the HOMO in 1, 2-diazonia-7, 8-diazabenzo[ ghi ]peryleneimide (TABPIm). Namely, the nitrogen lone-pair of electrons in the 7 and 8 positions of TABPIm, which are perpendicular to the ring plane ( i.e., part of π-system), induced an increased HOMO level. These results are successfully explained by DFT calculations and agree well with the spectroscopic and electrochemical results. With regard to the excited-state dynamics of these derivatives, the introduction of nitrogen atoms and/or an imide unit onto the BP core enables control of the rate constants of both the fluorescence and intersystem crossing (ISC) pathways, which significantly affects the corresponding quantum yields. The quantum yields of fluorescence ( Φ FL ) decreased with the introduction of nitrogen atoms, whereas an increasing trend of Φ FL was observed with substitution of an imide unit.